Ecklonia maxima: a potential NRF2 antioxidant modulator in Glucotoxicity-induced oxidative stress - Bekko, Adam (Stellenbosch : Stellenbosch University, 2025)
Thesis (MSc)--Stellenbosch University, 2025.